2020
DOI: 10.1016/j.plipres.2020.101036
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and regulation of thioesterases

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 230 publications
0
13
0
Order By: Relevance
“…Thioesters participate in metabolism, membrane synthesis, signal transduction and gene regulation. Thioesterases convert thioesters to the thiol and carboxylic acid components, which endorse thioesterases the important cellular roles (Swarbrick et al, 2020). This study demonstrated the native enzymes responsible for the hydrolysis of propionyl-CoA to propionate in the engineered P. putida strain.…”
Section: Enzymatic Characterization Of the Identified Thioesterase Pp_4975mentioning
confidence: 59%
“…Thioesters participate in metabolism, membrane synthesis, signal transduction and gene regulation. Thioesterases convert thioesters to the thiol and carboxylic acid components, which endorse thioesterases the important cellular roles (Swarbrick et al, 2020). This study demonstrated the native enzymes responsible for the hydrolysis of propionyl-CoA to propionate in the engineered P. putida strain.…”
Section: Enzymatic Characterization Of the Identified Thioesterase Pp_4975mentioning
confidence: 59%
“…Most genomes displayed less than seven GX lipases, except for G. boninense and G. leucocontextum with ten and nine GX lipases respectively. They are prominent enzymes catalyzing a wide range of reactions on various cellular substrates [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study reporting the three-dimensional cryo-electron microscopy structure of the recombinant type I FAS protein of Mycobacterium tuberculosis (which belongs to the CMN group bacteria), the narrow phylogenetic distribution of type I FAS systems in bacteria (only present in the genera Corynebacterium, Mycobacterium, and Nocardia), and the structural similarity between M. tuberculosis and fungal type I FAS, insinuates that an early horizontal gene-transfer event might have occurred from fungi to CMN bacteria. 115,124 Another hypothesis is that the CMN type I FAS represents an ancient type I FAS which further evolved in fungi and remained preserved in CMN bacteria 115 interestingly, mycolic acidproducing bacteria. 125 Comparative analysis between animal, fungal, and bacterial FAS showed that type I FAS systems are organized differently, with the main difference residing on the mechanisms of substrate shuttling during the process of fatty acid synthesis.…”
Section: Animal Fatty Acid Synthase: Architecture and Functionmentioning
confidence: 99%